Design and Simulation High Pass Filter Second Order and C-Type Filter for Reducing Harmonics as Power Quality Repair Effort in the Automotive Industry - Mochamad Irlan Malik; Eko Ihsanto (Journal of Integrated and Advanced Engineering (JIAE), 2023)
Electrical distribution is one of the most important parameters in industrial processes. Therefore, good power quality is needed as a supply to industrial machines. The use of industrial machines has an impact on the emergence of harmonics. As a result of the large Harmonics, the quality of power is getting worse, affecting productivity in the industry. Therefore, samples were taken using a Power Quality Analyzer on an 800 kVA transformer on the secondary side of the transformer to maximise the supply of electricity to consumers. Then obtained THDi Phase L1 of 23.1%, phase L2 of 24.7% and phase L3 of 21% and IHDi on the 5th order in phase L1 18.3%, phase L2 20.7% and phase L3 16.6% regarding (IEEE Std 3002.8-2018) and (SPLN D5.004-1:2012) the IHDi value should not be more than 7%. Then simulated using MATLAB/Simulink by designing the Second Order High Pass Filter and C-Type Filter. The results obtained by combining the two filters gained THDi results in the L1 phase at 2.53%, the L2 phase at 2.69% and the L3 phase at 2.22% and the IHDi at the 5th order of the L1 phase at 1.48%, the L2 phase 1.62% and L3 phase 1.33%.